2017
DOI: 10.1080/09273948.2017.1355471
|View full text |Cite
|
Sign up to set email alerts
|

Tocilizumab for the Treatment of Behçet Uveitis that Failed Interferon Alpha and Anti-Tumor Necrosis Factor-Alpha Therapy

Abstract: Tocilizumab may be a safe and effective therapeutic option for refractory BU.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(20 citation statements)
references
References 31 publications
0
17
0
3
Order By: Relevance
“…This has led to the clinical trials of tocilizumab, with several studies showing its efficacy in improving visual acuity and CME in cases of recalcitrant uveitis, with minimal adverse events associated with therapy . Multiple retrospective case series show similar results of efficacy and safety . A recent multicentre retrospective study on patients with JIA‐associated uveitis (refractory to ≥1 TNF‐α inhibitor) treated with tocilizumab showed that 88.2% of patients had complete control of ocular inflammation at 12 months .…”
Section: Il Blockersmentioning
confidence: 99%
See 1 more Smart Citation
“…This has led to the clinical trials of tocilizumab, with several studies showing its efficacy in improving visual acuity and CME in cases of recalcitrant uveitis, with minimal adverse events associated with therapy . Multiple retrospective case series show similar results of efficacy and safety . A recent multicentre retrospective study on patients with JIA‐associated uveitis (refractory to ≥1 TNF‐α inhibitor) treated with tocilizumab showed that 88.2% of patients had complete control of ocular inflammation at 12 months .…”
Section: Il Blockersmentioning
confidence: 99%
“…[85][86][87][88][89][90][91] Multiple retrospective case series show similar results of efficacy and safety. [92][93][94][95] A recent multicentre retrospective study on patients with JIA-associated uveitis (refractory to ≥1 TNF-α inhibitor) treated with tocilizumab showed that 88.2% of patients had complete control of ocular inflammation at 12 months. 93 There was a significant reduction in concomitant corticosteroid dosage and a statistically significant improvement in CMT and visual acuity.…”
Section: Il Blockers Tocilizumabmentioning
confidence: 99%
“…Tocilizumab, an anti-interleukin-6 (IL-6) receptor antibody, was used to treat 5 BU patients resistant to IFN-a and anti-TNF-a therapy, and all of the patients showed both clinical and angiographic improvement as well as a significant reduction in CMT. 99 Another molecule reported to be successful in treating resistant patients is golimumab, which is also an anti-TNF-a agent. It was shown to induce rapid regression of retinal vasculitis and reduce ocular episodes in 5 patients resistant to conventional and other biologic therapies.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, a clearing pars plana victrecomy may be considered for eyes that are unresponsive to medical therapy--especially when an epiretinal membrane is present and concomitant removal of that membrane may result in further restoration of vision. Six original articles [19][20][21][22][23][24] in this issue of Ocular Immunology & Inflammation address various aspects of the management of UME.…”
mentioning
confidence: 99%
“…Eser Ozturk et al 21 described the use of tocilizumab (TCZ), a fully humanized monoclonal antibody directed against both soluble and membrane-bound interleukin-6 (IL-6) receptor, in five subjects with Behçet uveitis who failed two to five years of treatment with conventional immunosuppression, interferon alpha, and anti-TNF therapy seen at a university center in Istanbul, Turkey. Drug was administered at a dose of 8 mg/kg as monthly intravenous infusion.…”
mentioning
confidence: 99%